PHISHING AWARENESS AND SECURITY CONCERNS: ANALYZING THE ROLE OF ANTI-PHISHING KNOWLEDGE AND INTERNET EXPERIENCE IN ONLINE BANKING USERS: Kesadaran akan Phishing dan Masalah Keamanan: Menganalisis Peran Pengetahuan Anti-Phishing dan Pengalaman Internet pada Pengguna Perbankan Online - Rista Junita Nur’aini; Megawati Simanjuntak (Faculty of Social Science and Human Ecology, IPB University, 2025)
Phishing has become Indonesia's most prevalent cybercrime from 2017 to 2022, primarily due to the collection of users' personal information. The purpose of this study is to examine how security concerns are impacted by social engineering, internet experience, anti-phishing expertise, and phishing awareness. The Technology Threat Avoidance Theory (TTAT) model lends credence to this study. A quantitative methodology was employed, conducted through online surveys. To enrich the discussion, six of these respondents participated in in-depth interviews as a complementary approach. Data analysis was performed using LISREL 8.80 and SPSS 26. The findings demonstrated that internet experience and anti-phishing knowledge significantly increased phishing awareness. Furthermore, security concerns were significantly impacted by anti-phishing expertise. The results of further analysis revealed that social engineering had no significant effect on phishing awareness. In addition, Internet experience did not significantly affect security concerns. Based on the research results, user understanding can be enhanced by creating educational media that can be disseminated via social media.